The Influence of Supervision on the Performance of Associate Nurse in Hospitals : a Literature Review - Munawar, Munawar; Saleh, Ariyanti; Rachmawaty, Rini (STIKes Surya Mitra Husada, 2019)
Background: Various efforts are made to maintain and improve the quality of nursing services, one of which is to carry out nursing care according to the standards of nursing practice safely, effectively and ethically. To maintain quality, it is necessary to control nursing care in a directed and planned manner. One of the controls in nursing management is supervision. Purpose: The purpose of this literature study is to identify the effectiveness of the implementation of supervision on the performance of implementing nurses in hospitals. Methods: Database searches used in this literature review are Pubmed, Science Direct and Google Scholar published in 2007-2018. Results: From the six articles used, it was found that supervision had an impact on improving nurses' performance in the form of actions and behaviors that could be measured to maintain and improve the quality of health services for both sick and healthy patients. Other impacts among them commitment, employee attachment, competence and individual quality as well as improving service qualityto them after completing the credentialing process as stated in the Nurse Clinical Assignment Letter. Conclusion: Implementation of supervision motivates nurses to be more attached to work, and has better performance opportunities